DAYA HASIL DAN MUTU BENIH PADI BERAS MERAH YANG DIBERI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK FOSFOR - Saputra, Zulfahmi '; Zuhry, Elza '; ', Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to determine the influence of the granting TKKS and fertilizer phosphorusagainst power result and quality of seed of red rice seed. This research has been carried out in the plant breeding laboratory in the faculty of agriculture, University of Riau, Tampan district, Pekanbaru in June to September 2016. The design of this research was a completely randomized block design (RAK), factorial (2 factors) and 3 replications. The first factor: compost TKKS (T) with 4 dosages (ton/ha) i.e. T1 (1.5), T2 (5), T3 (7,5), T4 (10) and the second factor: phosphorus fertilizer (B) with 4 doses (kg/ha): B1 (33.75), B2 (67.5), B3 (101,25), B4 (135). The data were analyzed using ANOVA andHSD 5%. The results showed that the application of 7.5 tonnes/ha of EFB compost and 101.25 kg/ha phosphorus gives the best results on most parameters such as the number of productive tillers, the amount of grain per panicle, the percentage of filled grain, dry milled per m2, 1000 seed weight and the germination rate. Application of 7.5 t/ha EFB compost TKKS tonnes /ha produce of 1.42 tonnes /ha, and applying 101.25 kg/ha phosphorus produce of 1.47 tonnes s/ha. Application of 7.5 t/ha EFB compost and 101.25 kg/ha of phosphorus produce the highest of red rice rice yield i.e. 1.58 tonnes /ha, but still much more downcast than the production of enormous potency. Keyword: TKKS compost, phosphorus fertilizer, the power result and quality of seed of red rice seed